Seventh-Grade Students' Difficulties in Learning English Verbs in the "My School Activities" Material - Leni Cahyani Mustapa; Moon Hidayati Otoluwa; Yunita Hatibie (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Previous studies on junior high school students' vocabulary learning have often examined vocabulary difficulties in general or discussed meaning, pronunciation, and usage separately. This descriptive qualitative study addresses that gap by investigating seventh-grade students' difficulties in learning English verbs in the My School Activities material at SMP Negeri 1 Bulango Timur through an integrated analysis of meaning, pronunciation, and contextual usage. Ten students were selected because they had studied the target material and represented varied English learning abilities. Data were collected through structured direct observation activities, namely verb-meaning matching, read-aloud pronunciation, and fill-in-the-blank sentence completion, supported by semi-structured interviews and documentation of the teacher's module and the English for Nusantara textbook. The data were analyzed using Miles, Huberman, and Saldana's interactive model through data reduction, data display, and conclusion drawing and verification. The findings show that all participants experienced difficulties across the three aspects. Students confused verb meanings and forgot previously learned words, pronounced verbs by relying on Indonesian spelling patterns, and selected verbs that did not fit sentence contexts. The study contributes a contextual account of how meaning, pronunciation, and usage difficulties are interconnected in verb learning and suggests that teachers should combine vocabulary review, read-aloud practice, and sentence-based activities.